Physics of tsunamis - Levin, Boris W. (Springer, 2017)
There has been significant progress in tsunami research, monitoring and mitigation within the last decade. This book summarizes the state-of-the-art knowledge on tsunamis. It presents a comprehensive overview of tsunamis, seaquakes and other catastrophic ocean phenomena. It describes up-to-date models of tsunamis generated by a submarine earthquake, landslide, volcanic eruption, meteorites impact, and moving atmospheric pressure inhomogeneities. Models of tsunami propagation and run-up are also discussed (...)